GENERAL AND MODERN TYPOLOGICAL TRENDS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper analyzes several modern typological trends in English, Uzbek, and Russian, focusing on grammatical structure, word-class classification, gender-neutral language tendencies, internet vocabulary, and neologism formation. The study highlights the analytical nature of English and the synthetic agglutinative structure of Uzbek, emphasizing their fundamental typological differences. It also compares the classification principles of word classes in both languages, noting the dominance of syntactic criteria in English and morphological-semantic criteria in Uzbek. The paper further explores the rise of gender-neutral expressions in modern English and the naturally gender-neutral system of Uzbek. Additionally, it examines the influence of English on Russian internet vocabulary, where widespread lexical borrowings and adapted digital terms illustrate global linguistic convergence. Finally, the typological features of word formation and contemporary neologisms in English and Uzbek are discussed, revealing the impact of globalization and digital communication on lexical expansion.